Cost‐of‐illness analysis of chronic urticaria clinical management in five countries of Latin America - Jorge Sánchez; Leidy Álvarez; José Ignacio Larco; Luis Ensina; Guillermo Guidos‐Fogelbach; Cesar A. Reyes‐López; German D. Ramon; Karla Robles‐Velasco; Ivan Cherrez‐Ojeda (Clinical and Translational Allergy)
Abstract Introduction Chronic spontaneous urticaria (CSU) is a disease with a high impact on the quality of life of patients. There are some evaluations of the economic cost of the disease in developed countries, but there is little information about the economic cost of the disease in developing countries. Our aim was to assess the economic diagnostic and therapeutic expenses of CSU in five Latin American (LA) countries. Methods A noninterventional multicenter cross‐sectional study was conducted in five LA countries: Brazil, Colombia, Ecuador, Mexico, and Peru. To determine the frequency of medical interventions as well as clinical and sociodemographic characteristics of CSU patients, questionnaires were administered to patients, primary care physicians, allergists, and dermatologists. In each country, diagnostics and therapeutic expenses were calculated by reviewing medical records, health insurance, and interviews. The main outcome was the yearly economic burden from the healthcare insurance perspective in each country. Results According to the projected costs, Brazil had the highest urticaria cost per patient/year (7009.4 USD), followed by Mexico (3695.1 USD), Ecuador (3132.8 USD), Peru (2693.9 USD), and Colombia (2392.8 USD); the cost and the frequency of use of omalizumab and antihistamines explain the total cost differences between countries. Interventions such as medical visits and exams had similar costs between countries and represented less than 10% of total urticaria cost analysis in the five countries. Conclusion The cost of the CSU in LA varies widely based on the health insurance coverage, the cost of the therapies, and the frequency of therapies used. Strengthening national health systems, as well as following the recommendations of international guidelines, seems to reduce the cost of CSU and improve the quality of patients.